Strong wet roll paper winding end adjusting and roll paper dispersing preventing device - HUANG RENHUAN (2021)
The invention relates to the field of strong wet paper processing, and particularly relates to a strong wet roll paper winding end adjusting and roll paper dispersing preventing device. The strong wet roll paper winding end adjusting and roll paper dispersing preventing device comprises a paper winding separation system, a support base, an operation control screen and the like; and the support base is connected with the operation control screen. The strong wet roll paper winding end adjusting and roll paper dispersing preventing device realizes fixed alignment of strong wet papers to prevent unevenness of two ends of roll papers caused by deviation of the papers in the winding process, meanwhile, fixes rupture places of the strong wet papers to prevent damage of structures of the sent strong wet roll papers, adjusts the end in secondary winding to prevent the effect of incapability of separating the whole roll papers due to partial overlapping caused by dislocation of the end of winding after secondary windin